The Efforts in Increasing Awareness and Identifiying Risk Factors of Cardiovascular Disease in Women - Mulyanti Roberto Muliantino; Yuanita Ananda; Yelly Herien; Bobby Febri Krisdianto; Esi Afriyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Cardiovascular disease is the primary cause of mortality among women on a global scale. However, the awareness among women regarding the risks associated with cardiovascular disease remains limited, leading to a delay in prevention, treatment, and, ultimately, mortality. This activity is intended to raise awareness and to identify those at high risk of developing cardiovascular diseases. The method uses an educational program and health screening involved 21 women in RT 02 RW 06 Pasar Ambacang, Padang City. The ABCD risk questionnaire was used to measure awareness. The result showed that respondents’ awareness score prior to the educational intervention was 37.5, which increased to 49.5 following the intervention. The health screening results indicated the presence of respondents with obesity (33.3%), overweight (19.1%), and non-ideal abdominal circumference (85.8%). Furthermore, the data revealed that 14.2% of respondents had stage 2 hypertension, 19.1% had stage 1 hypertension, 47.6% had pre-hypertension, 57.1% had high cholesterol levels, and 19.1% had high blood sugar levels. Educational efforts have been proven to increase awareness; moreover, health screening is effective in identifying the risk of cardiovascular disease in women. It is imperative that the female community is provided educational program to enhance their knowledge and awareness regarding disease risk.